#### Answer

\[m=-\frac{b}{a},\text{falls}\].

#### Work Step by Step

Take \[\left( {{x}_{1}},{{y}_{1}} \right)=\left( -a,0 \right)\]and \[\left( {{x}_{2}},{{y}_{2}} \right)=\left( 0,-b \right)\].
Slope of the line is:
\[m=\frac{{{y}_{2}}-{{y}_{1}}}{{{x}_{2}}-{{x}_{1}}}\]
\[\begin{align}
& m=\frac{-b-0}{0-\left( -a \right)} \\
& =-\frac{b}{a}
\end{align}\]
Therefore, the slope of the line is \[-\frac{b}{a}\].
There is a vertical change of \[-b\] units (\[b\]units down) for each horizontal change of \[a\] units.
The slope is negative. So, the line falls from left to right.